Pirazolo[1,5-a]pirimidinas: síntese e bromação - Scapin, Elisandra (2006)
The synthesis of a series of 2-methyl-7-trichloromethylpyrazolo[1,5-a]pyrimidines from the cyclocondensation reaction of 3-amino-5-methylpyrazole with 1,1,1-trichloro-4- alkoxyalk-3-en-2-ones [CCl3C(O)CH=C(R1)OR where R1 = H, Me, Et, Pr, Bu, t-Bu e R = Me, Et] in good yields (69-98%) is reported. Also, was performed the synthesis of 2- methyl-7-arylpyrazolo[1,5-a]pyrimidines from de cyclocondensation reaction of 3-amino-5-methylpyrazole with β-dimethylaminovinyl ketones [R2C(O)CH=CHNMe2, where R= Ph, Ph-4-NO2, Ph-4-Me, Ph-4-Br, Ph-4-F, Ph-4-Cl, pyrid-2-yl, pyrrol-2-yil, tien-2-yl e fur- 2-yl] in good yields (65-98%). Finally, was performed of the bromation reaction of 2- methylpyrazolo[1,5-a]-pyrimidines from the reaction of these compounds with Nbromosuccinimide (yields: 70-98%). All compounds were obtained in satisfactory purity and were identified by 1H, 13C, HMQC and HMBC spectroscopy, CG-MS and X-ray diffraction.